Дослідження технологій нанесення тактильних зображень на картонне паковання - Мельниченко, С. О.; Ігнатенко, Є. В.; Золотухіна, К. І. (ТОВ «Видавництво Ліра-К», 2025)
Technologies that can provide tactility on cardboard packaging and be useful for applying information for an audience with disabilities, research on measuring the characteristics of test elements and their reproduction on packaging products were identify.
Keywords: паковання; нанесення тактильних зображень